2019
DOI: 10.1002/btpr.2781
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive studies on optimization of cellulase and xylanase production by a local indigenous fungus strain via solid state fermentation using oil palm frond as substrate

Abstract: The high cost of cellulases remains the most significant barrier to the economical production of bio-ethanol from lignocellulosic biomass. The goal of this study was to optimize cellulases and xylanase production by a local indigenous fungus strain (Aspergillus niger DWA8) using agricultural waste (oil palm frond [OPF]) as substrate.The enzyme production profile before optimization indicated that the highest carboxymethyl cellulose (CMCase), filter paper (FPase), and xylanase activities of 1.06 U/g, 2.55 U/g, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 56 publications
(61 reference statements)
0
12
1
Order By: Relevance
“…Similarly, Tai et al (2019) reported the optimization of five physical and two nutritional parameters using the RSM approach for enhanced xylanase production. Indigenous fungus Aspergillus niger DWA8 was grown under SSF on an oil palm frond.…”
Section: Statistical Approach For Enhanced Xylanase Productionmentioning
confidence: 99%
“…Similarly, Tai et al (2019) reported the optimization of five physical and two nutritional parameters using the RSM approach for enhanced xylanase production. Indigenous fungus Aspergillus niger DWA8 was grown under SSF on an oil palm frond.…”
Section: Statistical Approach For Enhanced Xylanase Productionmentioning
confidence: 99%
“…Behnam et al [ 48 ] reported that the interaction between moisture and incubation time was significant for xylanase production by Mucor indicus and were non-significant for Mucor hiemalis and R. oryzae xylanase through SSF on wheat bran. In this sense, Tai et al [ 20 ], reported significant interaction between xylanase production and moisture level when A. niger DWA8 was grown using agricultural waste. According to studies conducted by Almeida et al and Azzouz et al [ 24 , 49 , 50 ], the interaction between the moisture level and incubation time does not significantly affect biomass and xylanase production by Penicillium roqueforti ATCC 10110, Trichoderma afroharzianum , and A. niger BG during solid-state fermentation of yellow mombin residue and wheat bran, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…RSM modeling strategies have been used for improving xylanase production by Aspergillus candidus [ 52 ] and A. fumigatus ABK9 [ 53 ] with wheat straw as the substrate, as well as other Aspergillus strains growing on related substrates [ 20 , 21 ]. Therefore, it may be concluded that BBD-based RSM strategies can significantly enhance xylanase production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the production of cellulases is very expressive owing to their various biotechnological applications. However their high cost, low titer of their production and low thermal stability of the produced enzymes remain the most significant barriers to their industrial applications [14][15][16]. therefore, microbial production of cellulase on local agriculture wastes represents a promising future for industrial applications with high environmental impact.…”
Section: Enzyme Activitymentioning
confidence: 99%